The Frequency and Risk Factors of Delayed Graft Function in living Donor Kidney Transplantation and Its Clinical Impact on Graft and Patient Survival in Part of Middle East - Nafar, Mohsen; Ahmadpoor, Pedram; Al Otaibi, Torki; E Alotaibe, Fahad; M Albugami, Meteb; Habhab, Wael; Abdulmajid dyab allawi, Ali; Dalili, Nooshin; Glotz, Denis (Urology Journal, 2020)
Delayed graft function (DGF) is a form of acute renal failure which results in increased post-transplantation allograft immunogenicity and risk of acute rejection episodes in addition to decreased long-term survival. Its incidence and risk factors have been extensively studied, especially after deceased donation. Until now, only few data has been published on DGF in living donor kidney transplant recipients. The present study was performed to investigate the frequency and risk factors of DGF among living- kidney transplant recipients. In this retrospective study, data had been collected from existing local hospital registries in three countries (Iran, Kingdom of Saudi Arabia (KSA) , and Kuwait ).